UPAYA PENYELESAIAN SENGKETA PADA SEKTOR BISNIS PARIWISATA DI TENGAH PANDEMI COVID 19 - N Nasrudin (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2020)
Tourism is one of the new style industries, which is able to provide rapid economic growth in terms of employment opportunities, income, standard of living and in activating other production sectors in tourist-receiving countries. While business is an activity to make a profit. In running a business, sometimes there are disputes between business actors and other business actors. Sometimes disputes that occur are due to a party defaulting and the other party feels disadvantaged. Broadly speaking, in Indonesia there are two pathways to resolve disputes namely litigation and non-litigation. The Litigation Path is a settlement effort made in the Court, while the non-litigation path is the settlement effort that is carried out outside the court. This study uses a type of library research, then this study uses a normative qualitative approach. The results of this study conclude that business disputes can occur at any time without exception when the outbreak of Covid 19. For example, the tourism business sector whose turnover has now declined dramatically because there are government regulations that require at home and not traveling. The decline in the turnover of the tourism business sector has made companies negligent, such as not paying full salaries to employees and being late in paying taxes. Such events can lead to disputes between companies and individuals. One of the efforts taken in resolving this dispute was mediation, while the mediation used was electronic mediation considering that the Covid 19 pandemic is not yet over.